Understanding the Role of Galectin-1 in Heart Failure: A Comprehensive Narrative Review - Sotoudeheian, Mohammad Javad; Mirahmadi, Seyed-Mohamad-Sadegh; Pirhayati, Mohammad; Azarbad, Reza; Nematollahi, Soroush; Taghizadeh, Mehdi; Pazoki-Toroudi, Hamidreza (Current cardiology reviews, 2024)
Heart failure (HF) is the fastest-growing cardiovascular condition worldwide. The immune system may play a role in the development of HF since this condition is associated with elevated pro-inflammatory cytokine levels. HF is a life-threatening disease, and there is an increasing demand for diagnostic biomarkers, prognostic factors, and therapeutic agents that can help treat it. Galectin-1 (Gal-1) is the prototype galectin of the lectin family. Multiple signal transduction pathways are regulated by Ras proteins, which act as a molecular switch in cells. Gal-1 regulates T and B cell activation, differentiation, and survival. Gal-1 has been linked to inflammation. Activated T cells produce Gal-1 through an autocrine apoptotic mechanism involving MEK1/ERK and p38 MAPK. In the cardiovascular system, atherosclerosis is facilitated by Gal-1. Heart disease, myocardial infarction, hypertension, and stroke can be caused by atherosclerotic plaque. HF and heart hypertrophy are caused by decreased cardiac L-type Ca 2+ channel activity. Deregulation of Gal-1 and CaV1.2 in pathological cardiac hypertrophy suggests a possible target for anti-hypertrophic therapy. Rat hypertrophic cardiomyocytes express Gal-1 and CaV1.2 channels simultaneously. It has been reported that diastolic dysfunction (DD) is associated with elevated Gal-1 levels. The high Gal-1 level in subjects led to the lowest cumulative survival as a composite endpoint. Incidences of HF, DD, and serum Gal-1 levels correlated significantly. The ejection fraction was negatively correlated with Gal-1 and CRP concentrations. Based on two different approaches in mice and humans, Gal-1 was identified as a potential mediator of HF.